2023
DOI: 10.1152/ajpregu.00228.2022
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause impacts cerebrovascular reactivity and brain structure

Abstract: Menopause is associated with adverse changes in vascular health coinciding with an increased risk of stroke and vascular cognitive impairment. However, there is significant variation in the age at menopause. The present study examined how the age at natural menopause impacts cerebrovascular reactivity and structural biomarkers of brain aging. Thirty-five healthy postmenopausal women were classified as early onset menopause (Early; n = 19, age at menopause: 47 ± 2 years) or later onset menopause (Late; n = 16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… 51 , 52 , 53 , 58 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 75 , 77 , 78 , 80 , 81 , 83 , 86 , 87 , 91 The remaining 18 studies were prospective or retrospective cohort studies. 54 , 55 , 56 , 57 , 59 , 62 , 72 , 73 , 74 , 76 , 79 , 82 , 84 , 85 , 92 , 93 , 94 , 95 In 203 patients with leukoaraiosis, Bian et al 91 demonstrated that patients exhibiting more severe white matter hyperintensities (Fazekas grades II and III) had a significantly reduced cerebrovascular reactivity compared with those with lower severity. In another larger cohort study, Staszewski et al 58 reported that in 120 subjects, the lowest tertile of cerebrovascular reactivity had a 19‐fold greater likelihood of having cSVD compared with the highest tertile.…”
Section: Resultsmentioning
confidence: 99%
“… 51 , 52 , 53 , 58 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 75 , 77 , 78 , 80 , 81 , 83 , 86 , 87 , 91 The remaining 18 studies were prospective or retrospective cohort studies. 54 , 55 , 56 , 57 , 59 , 62 , 72 , 73 , 74 , 76 , 79 , 82 , 84 , 85 , 92 , 93 , 94 , 95 In 203 patients with leukoaraiosis, Bian et al 91 demonstrated that patients exhibiting more severe white matter hyperintensities (Fazekas grades II and III) had a significantly reduced cerebrovascular reactivity compared with those with lower severity. In another larger cohort study, Staszewski et al 58 reported that in 120 subjects, the lowest tertile of cerebrovascular reactivity had a 19‐fold greater likelihood of having cSVD compared with the highest tertile.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies report reduced CBF and CVR following menopause, high-quality evidence and consistent menopausal criteria are lacking (Ruediger et al, 2021). A confounding factor is the impact of age and physical fitness at menopause age on cerebrovascular health (Chen et al, 2023;Moir et al, 2023;Ruediger et al, 2023). A recent systematic review of the influence of sex hormones on cerebrovascular function in human subjects suggested that, though there were often differences between high and low hormonal states, the directions were not consistent (Skinner et al, 2021).…”
Section: Oestrogen and Progesteronementioning
confidence: 99%
“…According to several studies, premature or early menopause is linked to cardiovascular disease, osteoporosis, type 2 diabetes, early cognitive function impairment, lower life expectancy, and increased mortality from all causes. [6][7][8][9][10][11][12][13] There are slight variations in the onset of natural menopause between ethnic groups, which are strongly influenced by genetics. 2,14 Other studies have shown that it is affected by ethnicity, region, and geographical country.…”
Section: Introductionmentioning
confidence: 99%